Sickness absence in compulsory and voluntary health insurance: the case of Sweden at the turn of the twentieth century. Issue 1 (2nd January 2017) - Andersson, Lars Fredrik; Eriksson, Liselotte
ABSTRACT: At the turn of the twentieth century, Swedish health insurance was organised according to the Western European models of both voluntary, 'fraternal' principles and compulsory, 'factory scheme' principles. In this paper, we trace the characteristics of both organisational forms, and compare the sickness absence by considering the role of risk selection and mitigation across a large panel of voluntary and compulsory health insurance societies operating in Sweden between 1900 and 1910. We find that voluntary societies used a wide set of rules and practices in order to select and monitor members in order to keep down the number of sick cases. Compulsory societies applied shorter waiting periods and offered more medical treatment, leading to more frequent but shorter sickness absences.